The Effect Of Ease Of Use And Product Safety On Increased Sales Through Customer Satisfaction: Systematic Literature Review (SLR) - Narotama Aulia Fazri; Budi Eko Soetjipto; Madziatul Churiyah (Economics and Business Journal (ECBIS), 2026)
This study aims to systematically analyze the influence of ease of use and product safety on sales increase with customer satisfaction as a mediating variable through a Systematic Literature Review (SLR) approach combined with bibliometric analysis. The research method uses a qualitative-descriptive approach with SLR techniques to identify, select, and analyze relevant scientific articles from various academic databases in a given publication period. The literature selection process is carried out through the stages of identification, screening, eligibility, and inclusion so that a number of articles that meet the inclusion criteria are obtained. Bibliometric analysis is used to map research trends, author collaborations, and developments on topics related to ease of use, product safety, customer satisfaction, and sales improvement. The results of the study show that the ease of use of products or services contributes significantly to the perception of value and customer comfort in using the product, which ultimately increases the level of satisfaction. In addition, product safety is also an important factor that affects customer trust so as to strengthen consumer satisfaction and loyalty. Customer satisfaction has been shown to play a role as a mediating variable that strengthens the relationship between ease of use and product safety to increased sales. The findings of this study confirm that companies need to optimize aspects of ease of use and product safety as a strategy to increase customer satisfaction and encourage sustainable sales growth. This study also makes theoretical and practical contributions in the development of marketing literature and consumer management, especially related to the integration of SLR approaches and bibliometric analysis in understanding the dynamics of factors that influence sales increases.